2021
DOI: 10.1101/2021.12.06.471235
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic interactions drive heterogeneity in causal variant effect sizes for gene expression and complex traits

Abstract: Despite the growing number of genome-wide association studies (GWAS) for complex traits, it remains unclear whether effect sizes of causal genetic variants differ between populations. In principle, effect sizes of causal variants could differ between populations due to gene-by-gene or gene-by-environment interactions. However, comparing causal variant effect sizes is challenging: it is difficult to know which variants are causal, and comparisons of variant effect sizes are confounded by differences in linkage … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
(74 reference statements)
1
6
0
Order By: Relevance
“…All four grandparents of each study participant also identified as Latino for GALA II or African American for SAGE. The median age of the participants varied from 13.2 (PR) to 16.0 (AA) years old. About 50% of the participants were female and 45% (MX) to 62% (PR) had physician-diagnosed asthma.…”
Section: Demographic Characteristics Of Gala II and Sage Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…All four grandparents of each study participant also identified as Latino for GALA II or African American for SAGE. The median age of the participants varied from 13.2 (PR) to 16.0 (AA) years old. About 50% of the participants were female and 45% (MX) to 62% (PR) had physician-diagnosed asthma.…”
Section: Demographic Characteristics Of Gala II and Sage Participantsmentioning
confidence: 99%
“…We and others have shown that gene expression prediction models trained in predominantly European ancestry reference datasets, such as the Genotype-Tissue Expression (GTEx) project 2 , have substantially lower accuracy to predict gene expression levels when applied to populations of non-European ancestry 3,12,13 . The importance of having ancestry-matched training datasets for prediction accuracy is also reflected by the limited cross-population portability of other multi-SNP prediction models, such as polygenic risk scores (PRS) [14][15][16] . Therefore, the limited diversity in genetic association studies and reference datasets is a major obstacle for applying existing integrative genomic studies to non-European populations.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed the prediction accuracy of polygenic scores for some traits was recently shown to be quite variable across different groups within an ancestry, suggesting that GxE and environmental variation are quite prevalent for some traits [ 45 ]. In addition, associated variants on the same haplotype were found to have differing effects in European–Americans and admixed African–Americans, suggesting that genetic or environmental interactions modify additive effect sizes across groups [ 47 ]. Thus, we caution that a better understanding of the portability of polygenic scores across populations also requires a stronger understanding of the causes of variation in prediction accuracy within populations.…”
Section: Discussionmentioning
confidence: 99%
“…For one, the associated loci are usually not the causal loci underlying trait variation; instead they tag the effects of linked causal sites. The interpretation of the effect size of an associated variant can be tricky because of: (i) linkage disequilibrium (LD), whereby it absorbs the effects at correlated causal sites [ 27 31 ]; (ii) population stratification, whereby it absorbs the effects of covarying environments [ 32 36 ]; and (iii) gene-by-environment (GxE) or gene-by-gene (GxG) interactions, whereby its estimate is averaged over the interacting environmental contexts or genetic backgrounds in the sample [ 28 , 37 47 ]. As all of these factors can and will vary across populations, the effect sizes of alleles will differ among them and so polygenic scores will have lower prediction accuracy, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Often, interactions are only tested between loci that are significant in single-locus GWAS or phenotypic variance test effects, or are based on hypothesized pathways or networks. While such methods improve feasibility by reducing the number of tests, they constrain the ability to detect novel epistatic effects or new pathways and networks involved in complex traits 8 , and in some cases do not indicate whether the interactor effect is an environment or a second gene 28,29 . Similarly, if a strong interaction between two loci exists, the main effects estimated in a single-variant GWAS could be muted 7 , reducing the likelihood of identifying such interactions in two-stage approaches.…”
mentioning
confidence: 99%